Strategi Pemerintahan dalam Implementasi Pengarusutamaan Gender di Kabupaten Tulang Bawang Tahun 2023 - Nurhana Putri Isna; Rejo, Samugyo Ibnu; Kartini, Dede Sri (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
(Government Strategy Through the Implementation of Gender Mainstreaming in Tulang Bawang District in 2023) This study aims to address the gap in public concern regarding gender inequality and injustice experienced by the community of Tulang Bawang Regency during 2022–2023, which arose due to the suboptimal implementation of gender mainstreaming (PUG). The research is conducted within the governmental environment of Tulang Bawang Regency, particularly at the Office of Women’s Empowerment and Child Protection (PPPA), focusing on the implementation of the gender mainstreaming program by regional government agencies, which is expected to achieve 100% coverage, with each agency implementing at least one gender-responsive program. This study employs a descriptive qualitative research method using both primary and secondary data, with informants selected through a purposive sampling technique. The results indicate that two stages have been successfully implemented, the action stage (direction) and the evaluation stage (learning). Meanwhile, the remaining three stages still require improvement, particularly the purpose stage, the environmental stage, and the direction stage, which have not yet adequately addressed existing gaps and the intended outcomes of the implemented actions. Abstrak ​​Tujuan (purpose) untuk mengatasi kesenjangan dalam kekhawatiran publik berupa ketidaksetaraan dan ketidakadilan gender yang dialami oleh masyarakat Kabupaten Tulang Bawang pada tahun 2022-2023 dikarenakan belum optimalnya pengarusutamaan gender (PUG). Melalui lingkungan (environments) pemerintahan Kab. Tulang Bawang khususnya Dinas PPPA dalam program pengarusutamaan gender yang dilakukan kepada Perangkat Daerah yang seharusnya mencapai 100% dengan arahan (directions) berupa setiap perangkat daerah memiliki minimal 1 program responsif gender. Menggunakan metode penelitian kualitatif bersifat deskriptif. Dengan menggunakan data primer dan sekunder serta memiliki teknik purposive dalam menentukan informan. Berdasarkan hasil penelitian, dua tahapan sudah dilalui dengan baik, yaitu tahapan aksi (directions) dan tahapan evaluasi (learning). Sedangkan tiga yang lainnya, masih memerlukan perbaikan, yaitu dari sisi tahapan tujuan (purposes), lingkungan (environments), dan pengarahan (directions) yang belum mengatasi kesenjangan dan apa yang ingin dicapai melalui aksi yang ada.